MANAJEMEN PENDIDIKAN KARAKTER PESERTA DIDIK DI SMK NEGERI 1 KOLAKA - laharini, laharini; Zakariah, Muhammad; Afifa, Rina Nur (Jurnal Teknologi Pendidikan Madrasah, 2020)
In the management of the character building of students carried out by the management of these educational institutions, by providing policies, namely every morning to read the Koran and read Asmaul Husna before the lesson begins, during the day the dhuhur prayer is carried out in congregation at the mosque of SMK Negeri 1 Kolaka, and the application of Islamic culture such as shaking hands when meeting teachers, smiling, appreciating guests and Islamic studies activities. Meanwhile, for students of different religions such as Christianity, Catholicism, and Hinduism, they adjust themselves according to their religious teachings. Based on the above background, and to find out the student character education management system implemented by the management of these educational institutions, the authors are interested in submitting a research thesis entitled: "Student Character Education Management at SMK Negeri 1 Kolaka". In this study, researchers used three triangulations, namely triangulation of sources, methods and investigators. Source triangulation is used by comparing the results of observation data, interviews and documentation. Method triangulation is done by collecting circulating data such as observation, interviews and documentation. Investigator triangulation bends the data obtained by an informant with other informants. Based on the results of this study, the researcher can conclude: Management carried out by the SMK Negeri 1 Kolaka school is in accordance with government rules and guidelines, covering several aspects including the planning, organizing, implementing and evaluating and the factors that support the implementation of character education for students at SMK Negeri 1 Kolaka, namely government support, adequate human resources (HR), complete school facilities and facilities, activities that have been programmed, a sense of kinship and support from all residents, both parents of students and the local community.